The Contribution of Observer towards the Teachers’ Performance in Classroom - Sri Damayanti; Jusriati Jusriati (Institut Agama Islam Negeri Palopo, 2019)
The aim of this paper is to describe the contribution of observer towards the performance of the teachers in teaching. The research question of this research is how is the teachers’ opinion about the contribution of the observer in their class? In answering the research question, the researchers conducted a research in a year by participating in learning community. The sample of this research is the students who have conducted Magang III and contributed as teacher. Here, the researchers use questionnaire given to the teachers. The data from the questionnaire analyzed in the form of Likert Scale. As a result of this study revealed that the fear is only a temporary concern because basically they concluded that the presence of observers had a positive impact on their performance, because there were many valuable lessons and input obtained from the presence of observers in their open classes and of course that will be material for further improvement of their learning. It can be seen from the percentage of the questionnaire show that from 14 statements, most of students are in the Strongly Agree and Agree range.